2018
DOI: 10.2478/johr-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chilling and Accumulative Photo-Thermal Units on Flowering of Strawberry (Fragaria × ananassa Duch.)

Abstract: The influence of chilling period hours and accumulative photo-thermal unit at different base temperatures, 10, 11, 13, 15, and 18 °C, on the flowering of strawberry was examined in Sana’a University-Yemen during two seasons: 2006 and 2007. The randomized complete block design (RCBD) field experiment was designed with 5 chilling hours (CHs) periods (0, 360, 750, 1080, and 1440 CHs under 2 ± 1 °C), with four replicates each. Accumulative photo-thermal unit (PTU) was calculated for every treatment at different ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…In our experiments carried out in unprotected strawberry orchards, the exogenous application of CKs caused an increase in the number of flowers and fruit size or weight, in treated plants, and this coincides with reports of other studies performed under protected conditions [45,[48][49][50][51][52][53][54]. Depending on the number of applications and concentration, CK applications have an evident influence on fruit formation, size, and weight, which could translate into an increase in yield.…”
Section: Exogenous Application In the Field Led To Changes In Flower ...supporting
confidence: 90%
“…In our experiments carried out in unprotected strawberry orchards, the exogenous application of CKs caused an increase in the number of flowers and fruit size or weight, in treated plants, and this coincides with reports of other studies performed under protected conditions [45,[48][49][50][51][52][53][54]. Depending on the number of applications and concentration, CK applications have an evident influence on fruit formation, size, and weight, which could translate into an increase in yield.…”
Section: Exogenous Application In the Field Led To Changes In Flower ...supporting
confidence: 90%
“…Previous studies also indicated that vernalization of Yemen native strawberry varieties at 2 • C for 15 days during the first growing season resulted in a greater number of flowers than non-vernalized treatments. The chilling hour requirement is the main factor that induces strawberry flowering: too little or too much can damage the plants and decrease flowering and fruiting [21]. In addition, vernalization of red raspberry 'Polka' at 6 • C resulted in a higher percentage of flowering than at 18 • C. Low temperatures led to faster flowering than high temperatures [22].…”
Section: Discussionmentioning
confidence: 99%
“…Wherever, the value of 10°C is a base tempera ture of strawberries (Almadhagi et al, 2018). In Fragaria vesca, higher temperatures were found to be critical for runner induction (Heide and Sønsteby, 2007).…”
Section: Temperature (T)mentioning
confidence: 99%
“…Flower initiation in strawberries requires chilling (Ito and Saito, 1962;Darrow, 1966;Kinet et al, 1993;Lieten, 1997;Almadhagi et al, 2018;Aldoubibi et al, 2021). For the best production and berry quality, both types of strawberries (EB and SB) required dif ferent amounts of chilling period before planting.…”
Section: Chilling Hour and Cold Storage (C)mentioning
confidence: 99%
See 1 more Smart Citation